The cup; and The falcon - Tennyson, Alfred Tennyson, Baron, 1809-1892 (Salt Lake City, UT : Project Gutenberg, 2023)
"The Cup; and The Falcon" by Alfred Lord Tennyson is a collection of dramatic works written in the late 19th century. The book includes two plays, "The Cup," a tragedy exploring themes of love, betrayal, and ambition set in the backdrop of Galatia, and "The Falcon," a romantic tale emphasizing loyalty and loss, set in an Italian landscape. Thematically, both works delve into complex human emotions and the consequences of personal choices amidst societal conflicts. In "The Cup," the story revolves around Synorix, a Galatian nobleman, who covets Camma, the wife of Sinnatus, the Tetrarch. As political tensions arise with the Romans, Synorix manipulates events to serve his ambition, which culminates in betrayal and tragedy. The narrative unfolds with Synorix$1 (Bs desperate attempt to win Camma's affection while navigating the dangerous political landscape of Roman dominance. In "The Falcon," Count Federigo has devoted his life to his noble falcon, which eventually becomes the centerpiece of a poignant exchange when Lady Giovanna, drawn back into his life, seeks the bird to heal her ailing son. Their interactions reveal the depths of love and sacrifice while also addressing the complexities of familial ties and social status. The play ends in a resolution that promises the melding of their lives, illustrating the redemptive power of love amidst personal loss. (This is an automatically generated summary.)s
Release date is 2023-12-04
Charlene Taylor and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive/American Libraries.)
Keywords: English drama -- 19th century